(untitled) (Academicia Globe: Inderscience Research, 2023)
The literature analysis of abdominoplasty is presented: the proposed numerous modifications of abdominoplasty can be summarized in the main types of surgical interventions: classical, vertical, combined and mini-abdominoplasty.